POPULATION AGEING AND THE TRAGEDY OF THE PENSION COMMONS - Schlett, András (Ekonomika, 2011)
The essay deals with sustainability issues of pension systems. Considering the functioning of the dividing–imposing systems, the definitive factors are the proportion and quality of active-age population and its willingness to pay pension contribution. It delineates the “prisoner’s dilemma” situation of the approach of childbearing in today’s social insurance pension systems. The fundamental problem with pension systems is that individuals with few or without children are in a better financial position by gaining more savings and having more time to spend on work which results in a higher pension income. Therefore, the dividing–imposing system erodes itself. The process is very similar to the tragedy of a theoretical common pasture described by Garrett Hardin. The most important lesson of the tragedy of commons is that individual rationality can lead to bankruptcy on the community level. Hardin was of the opinion that the tragedy of common pasture can be prevented by subdivision, namely privatisation. The present study examines the possible outcomes of the pension reform and what have been realised of these. The experience of the past decade demonstrates what confusion can be created and misinformation disseminated when the debate about the future of social security is left to those who have other interests than preserving an adequate social security protection.